The Relation of rs2981572 Polymorphism and IL-20 Levels in Asthma Patients Infected With Streptococcus - Mahmood Abbas, Hussein; Abdulla Hassan, Raghad; H. Abbas, Amer; Abed Nasser Dhabaan, Anwar (Al-Nahrain Journal of Science, 2025)
One frequent chronic autoimmune illness that affects many people is asthma. The current study examined the relationship between the genetic polymorphisms of interleukin 20 (rs2981572) and asthma chronic disorder among Iraqi patients who had Streptococcus pneumonia in both controls and cases. For the current study, 300 participants were split into two groups: a case group and a control group. In regard to patients, the blood and sputum specimens were collected together, while for the control group, only blood samples were collected. Each participant in the current work was given 8 ml of venous blood, which was then divided into two parts: 4 ml was immediately transferred into EDTA tubes for DNA extraction and detection of the rs2981572 polymorphism, and the remaining 4 ml of blood was put in a gel tube and left to clot for serum separation by centrifuge. To estimate IL-20, the enzyme-linked immunosorbent test was employed. IL-20 and rs2981572 were detected using the tetra-primers amplification refractory mutation system-polymerase chain reaction assay. According to the findings of the rs2981572 polymorphism, the genotypes TT (OR = 0.07; 95% CI = 0.04-0.12) were found to have highly significant protective factors (P = 0.0000). For the TG genotype, the P-value is highly significant, OR=9.54, 95% CI= 5.49–16.58, so the results suggested the TG genotypes are highly significant etiological factors and are associated with asthma disease as a risk factor. IL-20 levels in study population sera were found to be significantly higher in cases (P =0.0001) than in controls (1389.92 ± 31.84 vs. 797.67 ± 31.11 pg/ml) respectively.